Item-level and Composite-level Interrater Reliability of Functional Movement Screen™ Scores Following Condensed Training in Novice Raters - Brent A Harper (North American Sports Medicine Institute, 2021)
# BACKGROUND The Functional Movement Screen™ (FMS™) is a clinical instrument designed to use movement behaviors to screen individuals for injury risk. Current rater certification programs focus on extensive, individualized training, which may not be appropriate in all screening contexts.